2020
DOI: 10.3389/fpls.2020.01197
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Trait Genomic Prediction Improves Predictive Ability for Dry Matter Yield and Water-Soluble Carbohydrates in Perennial Ryegrass

Abstract: In perennial ryegrass (Lolium perenne L), annual and seasonal dry matter yield (DMY) and nutritive quality of herbage are high-priority traits targeted for improvement through selective breeding. Genomic prediction (GP) has proven to be a valuable tool for improving complex traits and may be further enhanced through the use of multi-trait (MT) prediction models. In this study, we evaluated the relative performance of MT prediction models to improve predictive ability for DMY and key nutritive quality traits, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
8
26
3
Order By: Relevance
“…MT-CV1 and ST-CV1 models showed similar predictive ability in most cases, consistent with many other studies [ 47 , 48 , 51 ]. This illustrates that MT models are not always better than the ST model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…MT-CV1 and ST-CV1 models showed similar predictive ability in most cases, consistent with many other studies [ 47 , 48 , 51 ]. This illustrates that MT models are not always better than the ST model.…”
Section: Discussionsupporting
confidence: 91%
“…MT-GS methods have recently been applied due to increased prediction accuracies when the correlated traits are incorporated into the model [ 36 , 37 , 40 42 ] and showed the improved predictive ability of GY in wheat by including physiological traits [ 42 45 ]. In addition to yield, MT-GS has also been used to improve the predictive ability of other traits such as grain end-use quality [ 46 ], dry matter yield and water-soluble carbohydrates [ 47 ], and baking quality [ 48 ]. The main objectives of this study were to compare the relative performance of ST and MT-GS models and determine whether incorporating in-season physiological traits (NDVI and CT) in prediction models can improve the predictive ability of primary traits including HI, GN, GY, FE, and SPI.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to MT-CV1, the MT-CV2 model significantly improved the PA for all agronomic traits in all the environments, suggesting that the inclusion of secondary traits in the training and testing sets improves the predictive performance of complex traits (Supplementary Tables 4, 5). Several studies have reported a similar improvement in prediction using the MT-CV2 model for agronomic and end-use quality traits in wheat (Rutkoski et al, 2016;Sun et al, 2017;Lado et al, 2018), rice (Wang et al, 2017), barley (Bhatta et al, 2020), sorghum (Fernandes et al, 2018), and ryegrass (Arojju et al, 2020). The MT-CV2 model outperformed the single-trait model for YLD prediction in all environments.…”
Section: Discussionmentioning
confidence: 67%
“…In this study, the PA of the MT-CV1 model was found similar to that of the ST-CV1 model for most of the trait-environment combinations in both growing seasons (Supplementary Tables 4, 5). Several studies have reported marginal or no improvement with MT-CV1, where information from secondary traits is limited to the training set (Calus and Veerkamp, 2011;Lado et al, 2018;Schulthess et al, 2018;Arojju et al, 2020;Bhatta et al, 2020). However, other studies reported an improvement in GP when the MT-CV1 model included secondary traits with moderate-high heritability (Jia and Jannink, 2012;Rutkoski et al, 2012;Guo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, ryegrass breeding methods are improving, new phenotyping [ 64 ] and genotyping techniques [ 57 ] are starting to deliver cost effective genomic selection [ 58 , 60 , 100 ] and these are being applied to improve endophyte stability and transmission [ 56 ]. Addition of hybrid breeding [ 61 ], self-fertility [ 101 ], along with gene editing technologies [ 102 ] will likely reduce variation between genotypes within a host germplasm (cultivar or F1 hybrid).…”
Section: Opportunities and Risks For The Futurementioning
confidence: 99%